The Impact of Chatgpt In Front-End Development With A Focus On Reactjs - Abubakar Bachtiar; Rian Andrian (Jurnal Media Computer Science, 2024)
This article analyzes the impact of using ChatGPT in front-end development with a focus on the ReactJS framework. Through interviews with front-end developers who have used ChatGPT, we evaluate their experience implementing ChatGPT in web application development with ReactJS.The results of the analysis show that using ChatGPT in front-end development, especially with ReactJS, has a positive impact. Developers report significant improvements in development speed, a wider range of idea exploration capabilities, and an increase in overall productivity. They appreciated ChatGPT's ability to provide coding suggestions and solutions that helped speed up the development process.However, several challenges were also identified. Developers find it difficult to control the output generated by ChatGPT, especially when it comes to understanding context and user preferences. In addition, depending completely on the ChatGPT model can be a risk if the model does not fully understand the demands of the project or generates inappropriate code.The implication of this research is that the use of ChatGPT in front-end development with ReactJS can increase the efficiency and creativity of developers, but it is necessary to consider the challenges and risks associated. Implementing ChatGPT in front-end development can provide huge advantages, provided developers are able to leverage it effectively and manage the resulting output.